Oropharyngeal Probiotic ENT-K12 Prevents Respiratory Tract Infections Among Frontline Medical Staff Fighting Against COVID-19: A Pilot Study - Wang, Qiang; Lin, Xuan; Xiang, Xiaochen; Liu, Wanxin; Fang, Ying; Chen, Haiping; Tang, Fang; Guo, Hongyan; Chen, Di; Hu, Xiafen; Wu, Qingming; Zhu, Baoli; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Healthcare workers at the frontline are facing a substantial risk of respiratory tract infection during the COVID-19 outbreak due to an extremely stressful work schedule and public health event. A well-established first line defense on oropharyngeal microbiome could be a promising strategy to protect individuals from respiratory tract infections including COVID-19. The most thoroughly studied oropharyngeal probiotic product which create a stable upper respiratory tract microbiota capable of preventing upper respiratory tract infections was chosen to evaluate the safety and efficacy on reducing episodes of upper respiratory tract infections for COVID-19 healthcare workers. To our knowledge to date, this is the very first study describing the beneficial effects of oropharyngeal probiotic been administrated by healthcare workers during the COVID-19 pandemic. In this randomized controlled trial, we provided the probiotics to frontline medical staff who work in the hospitals in Wuhan and had been in close contact with hospitalized COVID-19 patients for prophylactic use on a daily base. Our finding suggests that oropharyngeal probiotic administration significantly reduced the incidence of respiratory tract infections by 64.8%, with reduced the time experiencing respiratory tract infections and oral ulcer Symptoms by 78%, shortened the days absent from work by 95.5%, and with reduced the time underwent medication which is no record of antibiotic and anti-viral drugs intake in the probiotic group. Furthermore, medical staff treated with Bactoblis® experienced sustained protection from respiratory tract infections since the 10th days of oropharyngeal probiotic administration resulting in an extremely low incident rate of respiratory tract infections.